EVALUATING THE PROTECTIVE EFFECTS OF LOVASTATIN AGAINST DOXORUBICIN INDUCED CARDIOTOXICITY IN balb-c MICE - Sikandar, Abeera; Khalida Ajmal,; Ayesha Afzal,; Saima Rafique,; Ayman Zafar,; Tahira Tehseen, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Doxorubicin is one of the most commonly used anti-cancer drugs that treat a large number of haematological and solid malignancies. Its usage in dose and duration is nevertheless restricted by dose related organ damage, particularly cardiotoxicity. Lovastatin is a commonly prescribed drug for hypercholesterolemia and possesses remarkable antioxidant potential. Our study was aimed at evaluating and comparing its cardioprotective effect in two pre-treatment schedules against doxorubicin-induced cardiac damage. Methods: In this lab-based randomized controlled experiment, 40 BALB/c mice were randomly grouped into five groups (n=8). Group 1 served as control whereas Group 2 was given doxorubicin intraperitoneally at a dose of 10mg/kg. Group 3 received 10mg/kg of oral lovastatin for five days. Groups 4 and 5 were administered lovastatin for five and ten consecutive days correspondingly and doxorubicin was given on 3rd and 8th experimental days of these groups. Results: Doxorubicin caused a significant rise in cardiac enzymes; Creatine kinase MB (CK-MB) and Lactate Dehydrogenase (LDH) (p-value ‰¤0.0001) whereas cardiac histological alterations were ranked as moderate. The damage was significantly attenuated by lovastatin in the ten-day study design with a p-value of ‰¤0.001 for both LDH and CK-MB whereas a slightly less efficient restoration was observed in the five-day design with p-value of ‰¤0.001 for LDH and 0.012 for CK-MB. Histological preservation in both pre-treatment schedules was in accordance with the biological markers. Conclusion: In doxorubicin-based regimens, pretreatment for at least seven days with an easily available and safe statin can effectively prevent its potentially life-threatening cardiotoxicity.